2006
DOI: 10.1080/09640560600747554
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood impacts of the conversion of cropland to forest and grassland program

Abstract: Land use changes induced by the Conversion of Cropland to Forest and Grassland Program are found to provide farm households sampled in four counties from Shaanxi and Qinghai Provinces with increased net profits. This result is found to be robust for a range of discount rates and output price projections. The net present value of the difference in farm profits with and without the Program is found to be positive even when payments made under the Program are subtracted from with Program profits. Variations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Therefore, household food consumption began to depend less on the available land and more on market factors. From a nutritional perspective, residents of Inner Mongolia are generally well nourished, even for low-income families [2]. The food being consumed is also becoming more diverse, and this can encourage both grassland conservation and human health.…”
Section: Household Food and Fuel Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, household food consumption began to depend less on the available land and more on market factors. From a nutritional perspective, residents of Inner Mongolia are generally well nourished, even for low-income families [2]. The food being consumed is also becoming more diverse, and this can encourage both grassland conservation and human health.…”
Section: Household Food and Fuel Consumptionmentioning
confidence: 99%
“…Employment dependence ratio = On-farm employment/Total labor force (2) In this calculation, the total labor force excluded children in school or those who could not work (the disabled, the elderly and very young children). In this calculation, household survey data for onand off-farm employment were obtained and reported by herders or farmers from each household.…”
Section: Calculation Of Household Dependence On Local Grasslands Basementioning
confidence: 99%
See 1 more Smart Citation
“…Uchida et al (2005) found that the average household net income for the SLCP participants has increased significantly, ranging from 75% in Ningxia to 8% in Guizhou. Using separate survey data, Xie et al (2006) also found that the SLCP had a positive impact on recipients' revenue. However, Xu, Bennett, et al (2004), found that over the period of1999-2003, the growth rates in average net income vary greatly across the surveyed regions of their sample.…”
Section: Slcp's Socioeconomic Impactsmentioning
confidence: 94%
“…In addition, the program has promoted socioeconomic development that has helped numerous farmers change their income structure, thereby increasing their income (J. Liu et al, 2008;Uchida et al, 2005;Xie et al, 2006). The subsidy program focused on grain and cash because the primary consumption targeted by the SLCP was food consumption.…”
Section: Introductionmentioning
confidence: 99%